EVALUACIÓN DE DOS FORMAS DE COLECCIÓN DE SEMEN EN ALPACAS - Dávalos R., Rosa (2002)
Semen was collected from 10 alpaca males aged 3-6 years, 3 times weekly for 3 weeks, followed by a week of rest, overa 3 month period. A heated artificial vagina was used together with a dummy model anda female in heat. Semen was collected from all l O animals utilizing both procedures. Average copulation time was 15.9 ± 0.6 and 16.8 ± 0.7 minutes using the dummy and the receptive female (p>0.05). Sperm volume averaged 1.03 ± 0.04 and 1.73 ± 0.09 ml, (p<0.05); motility was 34.2 ± 5.3 and 68.9 ± 4.9 % (p<0.05); sperm concentration was 32.8 ± 4.3 and 57.5 ± 8.3 x 104 sperm/ml (p<0.05); live and abnormal spermatozoa were 34.3 ± 4.2 vs. 72.1 ± 1.9 % (p<0.05) and 14.9 ± 1.1 vs. 13.9 ± 0.7% (p>0.05) respectively. Semen collection using an artificial vagina in conjunction a receptive female was the most suitable procedure.